A natural gas hydrate system on the Exmouth Plateau (NW shelf of Australia) sourced by thermogenic hydrocarbon leakage. (January 2019) - Paganoni, Matteo; King, James J.; Foschi, Martino; Mellor-Jones, Katy; Cartwright, Joe A.
Abstract: The identification of natural gas hydrates and shallow free gas in sedimentary basins is critical for understanding the organic carbon cycle dynamics in the shallow geosphere, as well as for geohazard studies related to the development of commercial hydrocarbon fields. In this study, we report for the first time the evidence for the potential occurrence of a natural gas hydrate system along the continental margin of Australia, on the Exmouth Plateau (NW Shelf). By the use of high-quality 3D seismic data, calibrated by downhole data from ODP and industry boreholes, we interpret a series of shallow high-amplitude anomalies, including patchy bottom-simulating reflections, as the seismic expression of localised accumulations of free gas beneath the base of hydrate stability, and overlying high-saturation hydrates or authigenic carbonates. The hydrate-bearing reservoir is constituted by Neogene and Quaternary fine-grained carbonate nannofossil and foraminifera-rich oozes. The patchy distribution of the shallow free gas and hydrate accumulations, which reflects the geometry of deeper fault blocks, is hypothesised to result from the leakage of thermogenic gas from deeper reservoirs. The interpretation of a thermogenic origin for the hydrate-forming gases is supported by (1) the existence in the study area of several thermogenic gas discoveries within Late Triassic reservoirs, (2) seismic evidence of cross-stratal and stratal pathways for migrating gases in the overburden, (3) the presence of free gas accumulations at depths intermediate between the deep reservoirs and shallow gas hydrate systems, and (4) geochemical and lithological evidence that the conditions which favour the generation of shallow microbial gas are not present in the area. The acquisition of downhole log and sample data through the observed seismic amplitude anomalies is necessary to test the interpretations and hypotheses presented in this manuscript. Highlights: A natural gas hydrate system is interpreted to occur on the Exmouth Plateau. The hydrocarbon plumbing system is controlled by deep tectonic structures. Both cross-stratal and stratal pathways supply gas to the hydrate stability zone. The origin of the hydrate-forming gas is interpreted to be thermogenic. The gas hydrate reservoir is composed of nannofossil and foraminifera-rich oozes.